(untitled) (Proceeding Of Sari Mulia University Midwifery National Seminars, 2024)
Background :Postpartum care is very necessary because during the postpartum period maternal deaths often occur due to various problems such as bleeding and infection, this can occur due to poor postpartum care. Motivation is very important in a person because it influences the mother’s behavior in carrying out something to achieve a certain goal. The higher the postpartum mother’s motivation regarding self-care, the more independent she is in postpartum care. Independent self-care for postpartum mothers is very necessary, because during this period women experience many changes in themselves, both physically and psychologically Objective :Knowing the relationship between motivation and the level of independence of postpartum mothers in caring for themselves during the early postpartum in the working area of ​​the Padang Batung Public Health Center Design :Type of quantitative research with a cross sectional approach. The total sample was 30 postpartum mothers on days 1-7. The sampling technique uses accidental sampling. The data collection technique used a questionnaire, and analyzed using the Chi-Square testResults :The results of the research show that there is a relationship between motivation and the level of independence of postpartum mothers in caring for themselves during the early postpartum with a Chi Square test p-value of 0.003 Conclusion:There is a relationship between motivation and the level of independence of postpartum mothers in caring for themselves during the early postpartum. Health workers need to provide support in increasing the motivation of postpartum mothers to be independent in taking care of themselves